Students’ probabilistic thinking level in solving probability problems reviewed from Honey Mumford’s learning style - Khurrotul, A'yun; Masamah, Ulfa (Pusat Studi Pengembangan Pembelajaran Matematika, 2025)
Students' difficulties in solving probabilistic problems occur due to their lack of knowledge and understanding of probability concepts. Probabilistic thinking skills are essential to enhance students' ability to solve probabilistic problems in everyday life. This qualitative research aims to describe student’s levels of probabilistic thinking in solving probability problems reviewed from Honey Mumford's learning style. The research subjects consisted of eight ninth-grade students from a State Tsanawiyah Madrasah of Batu City. The primary instrument in this study was the researcher, supported by additional instruments such as probabilistic thinking test and a task-based interview guide. Data were collected through written tests, task-based interviews, and documentation. Data analysis was carried out using the constant comparative method which includes the stages of reduction, categorization, synthesis, and substantive theory preparation. The results showed that students with activist and pragmatist learning styles met all indicators at level 1 of subjective thinking, while reflector and theorist students showed wider variations up to level 3 if informal quantitative thinking and some at level 4 of numerical thinking. This finding implies that differences in learning styles contribute to student’s probabilistic thinking abilities at each level.